Review on bubble formation, rise and break-up in a gas-liquid system - Kulkarni, Amol A.; Joshi, Jyeshtharaj B. (Industrial & Engineering Chemistry Research, 2005)
The formation of gas bubbles and their subsequent rise due to buoyancy are very important fundamental phenomena that contribute significantly to the hydrodynamics in gas−liquid reactors. The rise of a bubble in dispersion can be associated with possible coalescence and dispersion followed by its disengagement from the system. The phenomenon of bubble formation decides the primitive bubble size in the system (which latter attains an equilibrium size), whereas the rise velocity decides the characteristic contact time between the phases which governs the interfacial transport phenomena as well as mixing. In view of their importance, we herein present a comprehensive review of bubble formation and bubble rise velocity in gas−liquid systems. The emphasis of this review is to illustrate the present status of the subjects under consideration and to highlight the possible future directions for further understanding of the subject. The bubble formation at a single submerged orifice and on multipoint sieve trays in Newtonian as well as non-Newtonian stagnant and flowing liquids is discussed in detail, which includes its mechanism as well as the effect of several system and operating parameters on the bubble size. The comparison of results has shown that the formulation of Gaddis and Vogelpohl22 is the most suitable for the estimation of bubble size in stagnant liquids. The special cases, such as bubble formation in reduced gravity conditions and weeping and in flowing liquids, are discussed in detail. The section on the rise of a gas bubble in liquid covers the various parameters governing bubble rise and their effect on the rise velocity. A comprehensive comparison of the various formulations is made by validating the predictions with experimental data for Newtonian as well as non-Newtonian liquids, published over last several decades. The results highlight that for the estimation of rise velocity in (i) pure Newtonian liquids, (ii) contaminated Newtonian liquids, and (iii) non-Newtonian liquids, the formulation based on the wave theory by Mendelson,190 Nguyen's formulation,155 and the formulation by Rodrigues,153 (last two, based on the dimensional analysis), respectively are the most suitable. The motion of bubbles in non-Newtonian liquids and the reason behind the discontinuity in the velocity are also discussed in detail. The bubble rise is also analyzed in terms of the drag coefficient for different system parameters and bubble sizes.